L'éducation au politique sur des questions socialement vives (QSV) liées au développement durable (DD) et aux objectifs de développement durable (ODD) - Alain Legardez; Maryse Cadet-Mieze; Agnieszka Jeziorski
To what extent the research work on socially acute questions (SAQs) may contribute to political education? Many authors interested in this topic are concerned with education for a political eco-citizenship from a transformative-critical perspective. We propose to illustrate these relationships by studying issues related to education for sustainable development (ESD), from a didactic perspective, and more specifically by the presentation-discussion of a collaborative training-action-research: the FECODD project (Training, Education and Skills and Sustainable Development Goals). How SD education - throughout the SDGs - may contribute to a better understanding and apprehension of the political issues that arise from it ?